2020
DOI: 10.3390/ma13214757
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ultra-High-Performance Concrete Compressive Strength Using Tabular Generative Adversarial Networks

Abstract: There have been abundant experimental studies exploring ultra-high-performance concrete (UHPC) in recent years. However, the relationships between the engineering properties of UHPC and its mixture composition are highly nonlinear and difficult to delineate using traditional statistical methods. There is a need for robust and advanced methods that can streamline the diverse pertinent experimental data available to create predictive tools with superior accuracy and provide insight into its nonlinear materials s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…However, it is worth mentioning that there are other ternative methodologies for predicting the mechanical behavior of SHCC, namely, mu The mentioned approaches have the appeal of using the micro-and mesomechanisms observed experimentally. However, it is worth mentioning that there are other alternative methodologies for predicting the mechanical behavior of SHCC, namely, multiphase modeling, in which the fibers are simulated discreetly and immersed in the cementitious matrix (Bitencourt Jr et al, 2019 [20], Qsymah, 2016 [21]; Cunha, Barros and Sena-Cruz, 2011 [22]); inverse analysis, in which the stress-strain relationship of the material is obtained by inverse analysis techniques based on experimental responses (Kang et al, 2010 [80]; Baby et al, 2013 [81], Stephen et al, 2019 [82]); use of different types of machine learning such as artificial neural network (ANN), support vector regression (SVR), classification and regression tree (CART), and gradient boosting tree (GBoost) (Guo et al, 2021 [83]; Abellán-García and Guzmán-Guzmán, 2021 [84], Marani, Jamali, Nehdi, 2020 [85]); and techniques based on the theory of homogenization with the development of multiscale models (Yu et al, 2020 [86]).…”
Section: Modeling Multiple Crackingmentioning
confidence: 99%
“…However, it is worth mentioning that there are other ternative methodologies for predicting the mechanical behavior of SHCC, namely, mu The mentioned approaches have the appeal of using the micro-and mesomechanisms observed experimentally. However, it is worth mentioning that there are other alternative methodologies for predicting the mechanical behavior of SHCC, namely, multiphase modeling, in which the fibers are simulated discreetly and immersed in the cementitious matrix (Bitencourt Jr et al, 2019 [20], Qsymah, 2016 [21]; Cunha, Barros and Sena-Cruz, 2011 [22]); inverse analysis, in which the stress-strain relationship of the material is obtained by inverse analysis techniques based on experimental responses (Kang et al, 2010 [80]; Baby et al, 2013 [81], Stephen et al, 2019 [82]); use of different types of machine learning such as artificial neural network (ANN), support vector regression (SVR), classification and regression tree (CART), and gradient boosting tree (GBoost) (Guo et al, 2021 [83]; Abellán-García and Guzmán-Guzmán, 2021 [84], Marani, Jamali, Nehdi, 2020 [85]); and techniques based on the theory of homogenization with the development of multiscale models (Yu et al, 2020 [86]).…”
Section: Modeling Multiple Crackingmentioning
confidence: 99%
“…In 2020, Marani A. et al [ 42 ] presented a solution to predict the compressive strength of ultra-high-performance concrete using a machine learning algorithm. They trained their algorithm on a database of 810 samples gathered from open-access sources.…”
Section: Concrete MIX Design and Machine Learningmentioning
confidence: 99%
“…Research has been continuously conducted to predict the strength of UHPC. Marani et al (2020) investigated a novel framework for predicting the compressive strength of UHPC using a tabular generative adversarial net model with 810 experimental data points from the literature [ 1 ]. Zhang et al (2017), Abuodeh et al (2020), and Nguten et al (2022) suggested an artificial neural network (ANN) model to predict the compressive strength of the UHPC [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%